Strategi Komunikasi Pemasaran Business-to-Business (B2B) PT Satukelas Adhyapana Nusantara dalam Meningkatkan Leads: (Studi Kasus pada Brevet Pajak) - Sabila, Sabila (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to analyze the business-to-business (B2B) marketing communication strategy by Brevet Pajak Satukelas in order to increase leads. The method used is a qualitative descriptive study with data collection through direct observation and in-depth interviews with SEM and the Training Director, as well as the Head of Marketing Brevet Pajak, and using the concept of The Marketing Communications Planning Framework to determine the marketing communication strategy carried out, from the planning stage to the evaluation. The results of the study show that the business-to-business marketing communication strategy of the Brevet Pajak program increased by 10-15% per month in acquiring leads, it was found that Brevet Pajak Satukelas uses three marketing communication strategies, namely pull, push, and profile. The push strategy aims to increase leads through a direct approach using Whatsapp and direct presentations. Then, the pull strategy aims to build initial interest and increase awareness. Meanwhile, the profile strategy aims to build the company's image and reputation through LSP ownership and collaboration with LSP and ATPI. Therefore, the main communication activities carried out by Brevet Pajak Satukelas are marketing communications and public relations.